Persepsi Penjaga Perlintasan Kereta Terhadap Shift Jaga Di Masa Pandemi Covid-19 Pada Daop 1 Jakarta - Dhina Setyo Oktaria (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2021)
This study discusses about train traffic and guard shifts in the covid-19 pandemic era whether it affects the perception of the  train crossing guard (PJL) performance in the work area. This reseach used quantitative and qualitative method where the questionnaire distributed to the train crossing guard (PJL) in the working area of Daop 1 Jakarta. The result of the study showed that Partial t test of calculated values and tables then the value t calculate > t table where the guard shift (X2) gives a positive influence on perception (Y), while train traffic (X1) has no influence on perception (Y). Simultaneous F test if the value of F calculates > F where F calculates = 15,683 is greater than F table 3.04 meaning that train traffic (X1) and guard shift (X2) simultaneously affect perception (Y) with a value of 14.4%.